Poems for the millennium : the University of California book of North African literature. - Joris, Pierre; Tengour, Habib (Poems for the millennium ;, 2012)
In this fourth volume of the landmark Poems for the Millennium series, Pierre Joris and Habib Tengour present a comprehensive anthology of the written and oral literatures of the Maghreb, the region of North Africa that spans the modern nation states of Libya, Tunisia, Algeria, Morocco, and Mauritania, and including a section on the influential Arabo-Berber and Jewish literary culture of Al-Andalus, which flourished in Spain between the ninth and fifteenth centuries. Beginning with the earliest pictograms and rock drawings and ending with the work of the current generation of post-indep.